SEASONAL AND SPATIAL VARIATION OF HEAVY METALS IN SEDIMENTS OF THREE CHILEAN BASINS - Sylvia Violeta Copaja; Roxana M. Tessada (Journal of the Chilean Chemical Society, 2020)
Total concentrations of heavy metals can provide information on sediment contamination levels. However, such information alone is insufficient to understand the mobility, bioavailability and toxicity of these elements in the sediment.  In this study we analyze the seasonal and spatial variation of labile fraction heavy metal concentration in three Chilean river basins. We also study the impact of mining nearby in the Cu concentrations in one of the sites studied in the three basins. Samples were taken in spring, summer, autumn and winter. Three selected basins were: Aconcagua (V Region), Cachapoal (VI Region) and Choapa (IV Region); sediments were collected at six different points of the river basins (E1-E6). For the labile orsoluble fraction of Al, As, Cd, Cu, Cr, Fe, Mn, Mo, Ni, Pb and Zn, 0.25 g of sediments were stirred with 40 mL acetic acid 0.11 mol L-1for 16 h at room temperature.  Metals were analyzed by ICP-OES. The eleven heavy metals analyzed in the labile fraction were detected in the three basins in most of the stations. The high concentration of Cu in the labile fraction found in the E2 site in the three basins demonstrates the influence of mining activities near this site. The mobility of Cu to other sites is depending on the characteristics of the basin. Variation between seasons was observed.